Собачье сердце - Булгаков Михаил Афанасьевич (Яркие страницы, 2022)
Экземпляры: Ф18 (20250520) / Инвентарный номер: 68130 / Цена: 200.00 / Сис.шифр: Р2 / Авт.знак: Б 90 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6